A Biology Laboratory Exercise Using Macromolecule Assays to Distinguish Four Types of Milk - Charlotte W. Pratt (American Society for Microbiology, 2011)
One of the drawbacks of cookbook-style laboratory exercises for General Biology courses is that students are not challenged to develop skills in scientific reasoning, such as formulating hypotheses and designing and carrying out experiments. Several traditional laboratory curricula include exercises involving semi-quantitative colorimetric assays to detect proteins (biuret test), reducing sugars (Benedict’s test), starch (Lugol’s test), and lipids (Sudan red test) in a variety of easily prepared solutions (glucose, albumin, glycine, etc.) and familiar food items (lemon juice, cornstarch, egg white, etc.). An extension of this lab exercise was developed to allow students to use their knowledge of the macromolecule assays to design an experiment to distinguish four types of “milk”: whole milk, skim milk, cream, and soy milk (rice milk or almond milk could also be included).